1980
DOI: 10.1113/jphysiol.1980.sp013210
|View full text |Cite
|
Sign up to set email alerts
|

Increased sodium appetite in the rat induced by intracranial administration of components of the renin‐angiotensin system.

Abstract: SUMMARY1. Intracranial injections of components of the renin-angiotensin system in rats in normal water and Na balance caused an immediate thirst followed by a progressive increase in Na appetite during a test session which lasted 18 h. The effect on water and Na intake was dose-dependent.2. Long-term (7 day) infusions of angiotensin II into the third cerebral ventricle at rates of 1 or 10 pmol h-' produced large and sustained increases in intake of water and 2*7 % NaCl. Intakes sometimes exceeded 100 ml 2-7 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
4

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(55 citation statements)
references
References 13 publications
(21 reference statements)
1
49
1
4
Order By: Relevance
“…Intracranial injection of Ang II stimulates the neural activity of sCVOs and induces water and salt intake (Buggy and Fisher 1974;Avrith and Fitzsimons 1980;Rowland et al, 1996;Sunn et al, 2003). Previous studies reported that some neurons in the sCVOs, where AT1a is abundantly expressed, are activated by systemic Na depletion (Fitzsimons, 1998) and that the neural activities in Na-depleted animals are supressed by intracerebroventricular injection of AT1a antagonists along with the reduction of salt-intake behaviors .…”
Section: Ii1 Introductionmentioning
confidence: 99%
“…Intracranial injection of Ang II stimulates the neural activity of sCVOs and induces water and salt intake (Buggy and Fisher 1974;Avrith and Fitzsimons 1980;Rowland et al, 1996;Sunn et al, 2003). Previous studies reported that some neurons in the sCVOs, where AT1a is abundantly expressed, are activated by systemic Na depletion (Fitzsimons, 1998) and that the neural activities in Na-depleted animals are supressed by intracerebroventricular injection of AT1a antagonists along with the reduction of salt-intake behaviors .…”
Section: Ii1 Introductionmentioning
confidence: 99%
“…The possible role of angiotensin in sodium appetite is less clear. There is good evidence that angiotensin infused directly into the brain stimulates sodium appetite (Avrith & Fitzsimons, 1980;Bryant, Epstein, Fitzsimons & Fluharty, 1980). However, unless there is a coexisting hypovolaemia, presumably providing a neural signal to sodium appetite, circulating angiotensin seems rather ineffective at stimulating increased intake of NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, repeated systemic injections of renin or of isoprenaline eventually produced the same moderate and consistent appetite for salt. When, in the subsequent experiments reported here, the hormone was infused continuously into the anterior third ventricle the appetite occurred in all animals and was never less than that seen after adrenalectomy despite the fact that all animals were probably in positive Na balance, as shown in the accompanying paper (Avrith & Fitzsimons, 1979), and in some rats was expressed in massive intakes of 3 0 % NaCl. At rates of 60 ng h-L to 6 jug h-1, 46 % of the animals drank at least 100 ml/day and 76 % drank at least 59 ml/day.…”
Section: Drinkometer Analysis Of Pattern Of Onsetmentioning
confidence: 99%